Body fat and circulating leptin levels in the captive short-beaked echidna (Tachyglossus aculeatus) - Kate J. Dutton-Regester; Alice Roser; Haley Meer; Andrew Hill; Michael Pyne; Aiman Al-Najjar; Tim Whaites; Jane C. Fenelon; Katherine L. Buchanan; Tamara Keeley; Marilyn B. Renfree; Stephen D. Johnston (Journal of Comparative Physiology B, 2024)
It is possible that the reproductive strategy of the short-beaked echidna is related to seasonal changes in fat deposition and energy availability, regulated by seasonal changes in endocrine function. We predicted that circulating leptin levels would be directly proportional to adiposity during most of the year, but that a change in this relationship would occur during the pre-breeding season to allow increased fat deposition. To test this hypothesis, we made use of a captive colony of echidnas to describe and quantify changes in fat distribution and the adipostatic hormone leptin. First we assessed seasonal changes in circulating leptin levels, body mass and adiposity for three male and three female adult echidnas maintained on a standard diet. Second, we explored the relationship between circulating leptin levels and increased caloric intake for an additional five adult female echidnas that were provided with supplemented nutrition. Third we visualised fat distribution in male and female adult echidnas using magnetic resonance imaging (MRI) before and after the breeding season, to determine where fat is deposited in this species. For echidnas maintained on the standard diet, there were no seasonal changes in body mass, body fat or plasma leptin levels. However, female echidnas provided with supplemented nutrition had significantly elevated plasma leptin levels during the breeding season, compared to the pre-and post- breeding periods. MRI showed substantial subcutaneous fat depots extending dorso-laterally from the base of the skull to the base of the tail, in both sexes. Pre-breeding season, both sexes had considerable fat deposition in the pelvic/rump region, whilst the female echidna accumulated most fat in the abdominal region. This study shows that male and female echidnas accumulate body fat in the pelvic/rump and the abdominal regions, respectively and that circulating leptin may promote fattening in female echidnas during the breeding season by means of leptin resistance. However, further research is required to evaluate the precise relationship between seasonal changes in leptin and adiposity.

Dual X-ray absorptiometry detects disease- and treatment-related alterations of bone density in prostate cancer patients - Gillian L. Smith; Alan P. Doherty; Linda M. Banks; Jane Dutton; Iain W. Hanham; Timothy J. Christmas; Richard J. Epstein (Clinical & Experimental Metastasis, 2000)